Sleep's benefits to emotional processing emerge in the long term. (November 2019) - Bolinger, Elaina; Cunningham, Tony J.; Payne, Jessica D.; Bowman, Marissa A.; Bulca, Ezgi; Born, Jan; Zinke, Katharina
Abstract: Sleep benefits the long-term preservation of emotional memories, making them accessible even years after the emotional episode has occurred. However, whether sleep also influences the emotional response that gets elicited while retrieving such memories (e.g., by increasing autonomic activity) remains unclear. Here, we demonstrate that sleep fosters a coherent decrease in both automatic (heart rate deceleration) and more cognitively controlled subjective measures (valence ratings) of the emotional tone associated with memories when they are retrieved after one week. Exploratory analyses suggest that sleep might initiate an enhancement of the neural representation of emotional compared to neutral memories (as reflected in the late positive potential of the electroencephalogram) that becomes pronounced after one week. These long-term effects are in contrast to sleep's immediate influence on the emotional response (i.e., 10 h after encoding), where heart rate deceleration was preserved and the late positive potential decreased when compared to the changes seen over a day of wake. Together, these results suggest that sleeping after an emotional experience has dynamic and protracted influences on the emotional tone associated with memories.